2010
DOI: 10.1080/17475759.2010.534860
|View full text |Cite
|
Sign up to set email alerts
|

Examining Chen and Starosta's Model of Intercultural Sensitivity in a Multiracial Collectivistic Country

Abstract: This study examines the applicability of Chen and Starosta's model of intercultural sensitivity in Malaysian culture using university student samples. A total of 447 randomly selected undergraduate students of a multicultural public university completed self-administered questionnaires. The study could not reproduce the five-factor structure formulated by Chen and Starosta. Instead, a three-factor structure (interaction attentiveness and respect, interaction openness, and interaction confidence) is devised fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 8 publications
1
37
0
5
Order By: Relevance
“…A CFA of ISS within Malaysian collectivistic setting by Tamam [14] failed to reproduce the five-factor structure; the model fit the data poorly. Hence EFA was applied to determine the dimensionality of the scale.…”
Section: Intercultural Sensitivity Scalementioning
confidence: 99%
See 4 more Smart Citations
“…A CFA of ISS within Malaysian collectivistic setting by Tamam [14] failed to reproduce the five-factor structure; the model fit the data poorly. Hence EFA was applied to determine the dimensionality of the scale.…”
Section: Intercultural Sensitivity Scalementioning
confidence: 99%
“…Tamam's [14] three-factor model indicated that ISS is not culture-free. Nonetheless, with high reliability coefficients and construct validity, the three-factor model is a promising alternative IS model for Malaysian context.…”
Section: Intercultural Sensitivity Scalementioning
confidence: 99%
See 3 more Smart Citations